Genetic variation in North America - Malhi, Ripan (Henry Stewart Talks, 2015)
Ethical & social implications of genetic research in indigenous communities, A multidisciplinary approach to infer evolutionary history, Genetic variation studies in Native Americans, Ancient DNA research to bypass genomic effects of European colonization, Non-indigenous admixture in Native Americans